KLRG1 expression induces functional exhaustion of NK cells in colorectal cancer patients - Cairui Xu; Kangli Cao; Along Ma; Meijuan Zheng; Yuanhong Xu; Ling Tang (Cancer Immunology, Immunotherapy)
Abstract Background Natural killer (NK) cells are a subset of innate lymphoid cells that possess cytotoxic properties, playing a pivotal role in immune surveillance against tumor cells. However, it remains unclear whether there are any alterations in the quantity and functional status of NK cells in colorectal cancer (CRC). Methods In this study, we collected peripheral blood samples from both CRC patients and age- and sex-matched healthy controls (HCs). The distribution characteristics, phenotypic changes, functional status, apoptosis susceptibility, and proliferative capacity of circulating NK cells were detected and analyzed by flow cytometry. An in vitro study was performed to investigate the blocking effect of KLRG1 antibody on peripheral blood NK cells in CRC patients. Results The frequency and absolute number of circulating NK cells were significantly decreased in CRC patients compared to those in HCs. Meanwhile, the function of NK cells from CRC patients was compromised, as shown by the reduced production of IFN-γ, TNF-α, and CD107a, with this impairment becoming increasingly significant as neural invasion progressed and tumor invasion advanced. We further found that the expression of activating receptors NKp30 and NKp46 were reduced, while the expression of inhibitory receptor KLRG1 was remarkably increased. The increased proportion of KLRG1 on NK cells was associated with CRC progression, and KLRG1+ NK cells showed impaired production of IFN-γ, TNF-α, and CD107a and were more susceptible to apoptosis. Importantly, blockade of the KLRG1 pathway could restore the cytokine production and degranulation ability of NK cells from CRC patients. Conclusions The present study demonstrates that NK cells in CRC patients exhibit functional exhaustion, and KLRG1 blockade restores the effector function of NK cells, indicating that targeting KLRG1 represents a promising strategy for immunotherapy in patients with CRC.